Analisis Sentimen Netizen Drama Korea â€œTrue Beautyâ€ Pada Twitter - Anis Fitri Nur Masruriyah; Elsa Elvira Awal (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2020)
K-Drama is widely liked by various cohorts, and provides inspiration in the work or motivates the lives of K-Drama enthusiasts. However, the opinion is not valid if the research has not been carried out or the opinion data has been processed properly. One of the K-dramas with the title "True Beauty" has a lot of fans because of the story that takes the theme of physical abuse. Because K-Drama is widely discussed in various media, it is necessary to analyze public sentimen towards this drama. From the tweets used in this study, with the VADER algorithm it is proven that "True Beauty" has a lot of enthusiasts and has received good responses.